PERLINDUNGAN HAK CIPTA TERHADAP PEMBAJAKAN KONTEN DI ERA DIGITALISASI - Muhammad Farhan; Anne Riski Ananda (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Copyright protection in the era of digitalization has become an increasingly important issue as cases of content piracy rise. Advances in information and communication technology have facilitated the dissemination of creative works, but they also pose new challenges for creators and copyright holders. This study aims to analyze the effectiveness of legal protection for copyright in Indonesia, particularly in the context of digital content piracy. The research employs a normative legal method with legislative and conceptual approaches. The findings indicate that although regulations exist, gaps between legal norms and practical implementation remain a significant obstacle. Furthermore, technological advancements such as artificial intelligence (AI) add complexity to copyright enforcement. Therefore, a synergy between stringent regulations, proactive corporate policies, and adaptation to technological developments is necessary to protect copyright and support the sustainability of the creative industry.